2022
DOI: 10.1007/s00170-022-10317-w
|View full text |Cite
|
Sign up to set email alerts
|

Airborne acoustic emission of an abrasive waterjet cutting system as means for monitoring the jet cutting capability

Abstract: Abrasive waterjet cutting is a manufacturing technology making use of a high-speed waterjet with abrasive particles in suspension, for cutting materials with different mechanical properties. Product quality requirements are pushing towards an improvement of tracking and stabilization methods of the relevant process variables. Amongst those, the jet kinetic power defines the cutting capability and has a significant impact on the final cut features. This variable is subject to relevant fluctuations versus time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A step ahead on the possibility to effectively monitor the jet cutting capability has been made with the study reported in [97], where the aim was to monitor the airborne acoustic emission [98] of an abrasive waterjet cutting head [99] and to investigate its correlation with the jet kinetic power [5]. The investigation was carried out by means of factorial studies, in which the jet was fired at various water pressures and abrasive feed rates, providing different kinetic powers.…”
Section: Airborne Acoustic Emission Monitoring To Assess the Waterjet...mentioning
confidence: 99%
“…A step ahead on the possibility to effectively monitor the jet cutting capability has been made with the study reported in [97], where the aim was to monitor the airborne acoustic emission [98] of an abrasive waterjet cutting head [99] and to investigate its correlation with the jet kinetic power [5]. The investigation was carried out by means of factorial studies, in which the jet was fired at various water pressures and abrasive feed rates, providing different kinetic powers.…”
Section: Airborne Acoustic Emission Monitoring To Assess the Waterjet...mentioning
confidence: 99%